"Unwarranted survivals" and "anomalous deaths" from coronary heart disease: prospective survey of general population. Issue 7327 (22nd December 2001) - McConnachie, Alex; Hunt, Kate; Emslie, Carol; Hart, Carole; Watt, Graham
Abstract: Objectives: To assess survival in people who are at apparent high risk who do not develop coronary heart disease ("unwarranted survivals") and mortality in people at low risk who die from the disease ("anomalous deaths") and the extent to which these outcomes are explained by other, less visible, risk factors. Design: Prospective general population survey. Setting: Renfrew and Paisley, Scotland. Participants: 6068 men aged 45–64 years at screening in 1972-6, allocated to "visible" risk groups on the basis of body mass index and smoking. Main outcome measures: Survival and death from coronary heart disease by age 70 years. Results: Visible risk was a good predictor of mortality: 13% (45) of men at low risk and 45% (86) of men at high risk had died by age 70 years. Of these deaths, 12 (4%) and 44 (23%), respectively, were from coronary heart disease. In the group at low visible risk other less visible risk factors accounted for increased risk in 83% (10/12) of men who died from coronary heart disease and 29% (84/292) of men who survived. In the high risk group 81/107 who survived (76%) and 19/44 (43%) who died from coronary heart disease had lower risk after other factors were considered. Different risk factors modified risk (beyond smoking and body mass index) in the two groups. Among men at low visible risk, poor respiratory function, diabetes, previous coronary heart disease, and socioeconomic deprivation modified risk. Among men at high visible risk, height and cholesterol concentration modified risk. Conclusions: Differences in survival between these extreme risk groups are dramatic. Health promotion messages would be more credible if they discussed anomalies and the limits of prediction of coronary disease at an individual level.